Birds as key vectors for the dispersal of some alien species: Further thoughts. Issue 5 (9th March 2017) - Reynolds, Chevonne; Cumming, Graeme S.; Vilà, Montserrat; Green, Andy J.
Abstract: W. Solarz, K. Najberek, A. Pociecha & E. Wilk‐Woźniak (2017, Diversity and Distributions, 23, 113–117) published a letter in Diversity and Distributions debating our view that waterbirds are important vectors of alien species (C. Reynolds, N. A. F. Miranda & G. S. Cumming, 2015 Diversity and Distributions, 21, 744–754; A. J. Green, 2016 Diversity and Distributions, 22, 239–247) and question whether future research into the mechanisms under‐pinning this phenomenon can be advantageous for the practical management of alien species. Additionally, Solarz et al. suggest that human activities are the primary source of all alien species introductions and that waterbirds may only act as vectors of secondary dispersal. In this letter, we respond to several arguments raised by the authors surrounding the relevance of waterbird‐mediated dispersal in the introduction and spread of alien species. We emphasize the partly deterministic nature of waterbird dispersal and the significance of long‐distance dispersal events (and hence the potential for primary introductions of new alien species across political boundaries). Finally, we reaffirm the importance of further research into dispersal by birds to improve our capacity to foresee and manage invasions of those alien species with strong capacity to spread via avian vectors.